"Og dermed ligestillede": Hovedstadslønarbejderklassen i det 20. århundredes første halvdel - Bro, Henning (Arbejderhistorie - tidsskrift for historie, kultur og politik, 2025)
this article has shown that in the first half of the 20th century, a steadily growing working class and a rapidly growing lower-level civil servant class were formed in in the capital. Behind this was not only the continued industrialization of the period, but also the concentration of capital that was behind this process and was also embedded in the development of the capitalist market economy. Decisive for a growing private administrative sector, which included other manual tasks that were not directly part of production, but were crucial for it, as well as simple and routine administrative functions. tasks and functions that were carried out by a lower layer of civil servants who at most had a vocational education and were not granted any form of management powers. With the simultaneously emerging welfare state, corresponding tasks and functions were generated at the same time in the state and municipality and thus also the basis for the increase in the number of lower-level civil servants. By analyzing the living conditions indicators that the public statistics of the time provided insight into, the article has also documented that the working class and the lower-level civil servant class were subject to the same living conditions in terms of income, consumption patterns, housing conditions and, in all likelihood, also access to the school system, that gives exams, and cultural life. Together with the work-related functions, a distribution of living conditions that proves that a growing wage-earning class was formed in the capital of the period, comprising the working class and the lower-level civil servant class. The basis for the establishment of the early welfare state was a target group that was designated as “workers and thus equals”. A wage-earning class, as the article demonstrates, gradually came to include more than three-quarters of the working-age population in the capital and the provincial market towns, and which, together with the gradually established legal principle, argues that the welfare state acquired the universalistic character, traditionally attributed to the post-war welfare state, before the middle of the century. In this context, the article finally points out features of how the labor movement, through its trade union and corporate organizations and its political class alliance with homesteaders in the construction of the early welfare state in the period, attempted to create greater social equality through higher real wages, shorter working hours, and better living conditions for the very large population segment that made up the wage-earning class. greater equality, which the article argues for to a certain extent, was achieved in the period in terms of wages and hours, consumption patterns, and housing conditions, but not in terms of access to the school, that provides exams, and culture.